Uzávěr ouška levé síně systémem AtriClip - Mokráček, Aleš; Kurfirst, Vojtěch; Bulava, Alan; Haniš, Jiří (Vnitrni lekarstvi, 2017)
INTRODUCTION: Atrial fibrillation (AFib) is related to a high risk of stroke. The main role in etiopathogenesis is played by the left atrial appendage (LAA). As many as 95 % of thrombi in nonvalvular atrial fibrillation are located in the appendage. Prevention of stroke then consists in permanent anticoagulation which, however, has its limits and risks. An alternative method is the left atrial appendage occlusion. In our report, we would like to present a new possibility of the closure using the epicardial system AtriClip (AtriCure). METHODOLOGY: In the period beginning in July 2012 - September 2015 we performed LAA closure in 101 patients. A mean age of 65 ± 6 years, 47 women, CHA2DS2 VASc (Ø) 2.47 (0-6). Monitoring 1 837 (Ø 18.5) months. A concomitant procedure was performed in 37 patients, endoscopic MAZE plus clip in 57 patients, and 7 patients underwent stand-alone implantation of the clip. The clip was implanted from full sternotomy, minitoracotomy or through thoracoscopy. Clip loading, residual recess and endoleak were assessed through endoscopic ultrasound according to the Cleveland criteria. RESULTS: The perioperative success rate of loading reached 98 %. The clip was loaded with a neck greater than 1 cm in 2 patients. No migration of the clip occurred, no endoleak was detected and no thrombus at the appendage base was detected. One case of periprocedural stroke was recorded. Within follow-up monitoring TIA occurred in 4 patients and no stroke was recorded. CONCLUSION: Epicardial LAA occlusion using the AtriClip system is a safe and reproducible method of LAA occlusion and an important alternative in the prevention of stroke.Key words: atrial fibrillation - occlusion of left atrial appendage - stroke.
Keywords: senioři; torakoskopie; Stroke; Sternotomy; Thoracotomy; Tomography, X-Ray Computed; Time Factors; Atrial Appendage; výsledek terapie; trombóza; Middle Aged; mužské pohlaví; Surgical Instruments; Cardiac Surgical Procedures; Thrombosis; cévní mozková příhoda; Thoracoscopy; síňové ouško; ženské pohlaví; chirurgické nástroje; Humans; kardiochirurgické výkony; sternotomie; fibrilace síní; časové faktory; lidé středního věku; torakotomie; počítačová rentgenová tomografie; Aged; Atrial Fibrillation; Female; Treatment Outcome; lidé; Male